2008
DOI: 10.1002/bjs.6297
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of proximal versus distal laparoscopic gastric bypass for morbid obesity

Abstract: Background: Laparoscopic gastric bypass is the 'gold standard' for treatment of morbidly obese patients in many centres. There is debate regarding the optimal length for small bowel limbs. This study aimed to determine whether the proximal or distal approach is better.Methods: Twenty-five patients undergoing primary distal gastric bypass in 2000-2002 were randomly matched for age, sex and preoperative body mass index (BMI) with 25 patients having a primary proximal bypass. All distal operations were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
4
41
4
Order By: Relevance
“…An increasing body of evidence in humans indicates that up to certain limits the size of the gastric pouch and length of the different limbs is of less importance for the outcome of gastric bypass [28]. In support of this observation, we demonstrated that the level of restriction measured by the size of the gastro-jejunostomy has no impact on different levels of weight loss and food intake after gastric bypass in rats.…”
Section: Discussionsupporting
confidence: 77%
“…An increasing body of evidence in humans indicates that up to certain limits the size of the gastric pouch and length of the different limbs is of less importance for the outcome of gastric bypass [28]. In support of this observation, we demonstrated that the level of restriction measured by the size of the gastro-jejunostomy has no impact on different levels of weight loss and food intake after gastric bypass in rats.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, the reduction after distal gastrectomy was 11.4 % on average (data not shown), which was also slightly larger than in other studies [13,14]. Weight loss is considered a risk factor for internal hernia in RYGBP [15,16]. The large decrease in mesenteric fat after distal gastrectomy is a major cause of weight loss after surgery [17,18].…”
Section: Resultssupporting
confidence: 39%
“…An ideal management of super-obese patients does not exist, but gastric bypass is one of the most common procedures with the best results concerning efficacy, morbidity and mortality [1][2][3][4][5][6][7]. If a decision for gastric bypass is made after the relevant preoperative diagnostics (body mass index, comorbidities, diabetes mellitus), the surgeon has a choice between Roux-en-Y and B-II gastric bypass.…”
Section: Introductionmentioning
confidence: 99%